2007
DOI: 10.1001/jama.297.20.2201
|View full text |Cite
|
Sign up to set email alerts
|

Sulfadoxine-Pyrimethamine, Chlorproguanil-Dapsone, or Chloroquine for the Treatment of Plasmodium vivax Malaria in Afghanistan and Pakistan

Abstract: clinicaltrials.gov Identifier: NCT00158561.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
1
53
0
1
Order By: Relevance
“…Drugs that result in a slow and incomplete clearance of asexual parasitemia result in a longer duration of gametocyte carriage. For P. vivax, treatment with SP, against which high-level P. vivax resistance is reported (362), and antibiotics results in longer gametocyte carriage than that with more efficacious antimalarial drugs (248,362,364,365). Similar to the case for P. falciparum, P. vivax gametocytemia after treatment may serve as a predictor for the later reappearance of asexual parasites (189,365).…”
Section: Antimalarial Drugs and P Vivax Gametocytemiamentioning
confidence: 94%
“…Drugs that result in a slow and incomplete clearance of asexual parasitemia result in a longer duration of gametocyte carriage. For P. vivax, treatment with SP, against which high-level P. vivax resistance is reported (362), and antibiotics results in longer gametocyte carriage than that with more efficacious antimalarial drugs (248,362,364,365). Similar to the case for P. falciparum, P. vivax gametocytemia after treatment may serve as a predictor for the later reappearance of asexual parasites (189,365).…”
Section: Antimalarial Drugs and P Vivax Gametocytemiamentioning
confidence: 94%
“…A number of reliable studies involving large numbers of patients in both Thailand (59,125,136,217,229) and India have shown almost uniform susceptibility to chloroquine in vivax malaria (154,226), although very recent work from the Gujarat State in western India found a 91% success rate among 65 evaluated patients (209). Studies in Pakistan, Afghanistan, and Azerbaijan have shown little or no evidence of resistance (121,134,227). Reports from Turkey showed 85% to 90% susceptibility (129), but a more recent survey from the southeastern sector showed only 78% susceptibility (130).…”
Section: Distributionmentioning
confidence: 99%
“…Therefore, some proportion of the P. vivax population is often inadvertently exposed to SP selection pressure, and this might have caused the selection of SP-resistant alleles in P. vivax isolates. It has been considered that P. vivax is intrinsically resistant to pyrimethamine (4), but a high therapeutic efficacy of SP has also been reported (5).…”
mentioning
confidence: 99%